Urban area development a case study of the relocation of the poor of Iloilo River - Oracion, Connie Jane D.
The burgeoning number of slums and informal settlements has become an alarming worldwide scenario and Iloilo City is not an exemption to this problem. The informal settlement site in North San Jose has been proven to be under slum condition using the indicators laid out by the United Nations. With the recent plan of the government to rehabilitate the Iloilo River, it aims to improve the lives of informal settlements affected by the plan and address the problem of insecurity of tenure. The relocation of these informal settlers spells a better living condition, hence human development. The initiative to rehabilitate the river is a sign that the government acknowledges the fact that the environment plays an integral factor in the development of the city and incorporating sustainable development in their development plans.